Evaluation of the components of internal control in the warehouse area of the Provincial Municipality of San Martín - Rumaldo-Berna, Uldarica D. (2019)
The present investigation "Evaluation of the components of the Internal Control in the warehouse area of ​​the Provincial Municipality of San Martín", had like objective determine to what extent the components of the internal control system are related to the activities of the warehouse area in the Provincial Municipality. In this way the investigation has allowed to know the important role of internal control in its position of guarantor of compliance with the law, defender of legality and not to act on the undue persecution of honest employees and officials but to establish the deviations that entail the administrative, criminal and civil responsibility of the bad employees and officials of the institution. The study approach was quantitative, with a non-experimental, transversal design. The instrument used was the questionnaire with an attitude scale (Likert scale) that was applied to the selected sample, which consisted of 28 public officials. The data was processed using the technique of descriptive statistics, the hypothesis testing was performed by the non-parametric statistical test of the Chi-square, obtaining as value X2 = 67.32142857 and the critical value was (X2C = 50.9985), therefore, it is concluded that the Internal Control components influence the activities of the warehouse area.